Integrating Sustainability into Financial Management Practices: An Indian Scenario - Sakasnamam, Sivanraj (Digital Repository of Theses, 2026)
This study investigates investor perspectives on sustainable financial management (SFM) and the key determinants influencing sustainability-oriented investment decisions in India. As sustainable investing gains prominence globally, a critical knowledge gap remains regarding investor awareness, perceived risks, and motivations specific to emerging economies like India. To address this, a mixed-methods research design was adopted, comprising 300 structured surveys and 20 in-depth interviews with institutional investors, self-directed investors, and policymakers. Quantitative analysis, including regression and ANOVA, revealed a strong positive correlation (R = 0.895, R² = 0.802) between investor awareness of SFM and sustainable investment decision-making, signifying that greater awareness directly enhances sustainable behaviors. Additionally, a high correlation (r = 0.903) was found between sustainable finance practices and risk management, underscoring their interdependence. The study also identified key motivational drivers such as ethical values, long-term profitability, and regulatory incentives, along with barriers like data limitations and perceived financial trade-offs. Qualitative insights further highlighted that external factors, including market trends and ESG policies, significantly influence investor behavior. The findings imply that targeted investor education and regulatory alignment could accelerate sustainable investment adoption while strengthening firms’ risk mitigation capacities. This research contributes original empirical evidence from India, a major emerging market, offering a scalable framework for understanding how awareness, risk perceptions, and policy contexts shape sustainability in financial decision-making. It underscores the need for integrated strategies that promote sustainable finance while addressing its associated implementation challenges.